Travels through the interior provinces of Columbia (1827)
This publication is a journal of his experiences with different trips conducted by the author for the inland provinces of Colombia. / Abstract. Esta publicación es un diario de los diferentes viajes con sus vivencias que realizó el autor por las provincias de Colombia.